Optimalisasi fintech untuk mempeluas jangkauan lembaga keuangan dalam membangun usaha mikro dan kecil menengah - Fauzi, Moh. (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the role of optimizing financial technology (fintech) in expanding access to financial services for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Although MSMEs have an important role in the national economy, they still experience various obstacles, especially in obtaining financing from traditional financial institutions. Fintech offers alternative solutions through innovations such as peer-to-peer (P2P) lending and crowdfunding, which allow MSMEs to gain access to capital with easier requirements and faster processes compared to conventional financial institutions. This study uses a qualitative approach with a literature review method to evaluate various studies related to fintech and its impact on MSMEs. The results of the study show that fintech has the potential to increase financial inclusion for MSMEs, especially in terms of capital and transaction efficiency. However, obstacles such as low financial literacy and limited technological infrastructure in remote areas remain major challenges. Therefore, collaboration between the government, financial institutions, and fintech providers is needed to create an inclusive and sustainable financial ecosystem for the development of MSMEs in Indonesia.